BRCA1 and BRCA2 mutation testing in Cyprus; a population based study. Issue 4 (23rd November 2016) - Loizidou, M.A.; Hadjisavvas, A.; Pirpa, P.; Spanou, E.; Delikurt, T.; Tanteles, G.A.; Daniel, M.; Kountourakis, P.; Malas, S.; Ioannidis, G.; Zouvani, I.; Kakouri, E.; et al.
Abstract : This paper presents the largest study in Cyprus evaluating the frequency and distribution of BRCA1 / 2 mutations in a high risk patient cohort. Deleterious mutations in the BRCA1 / 2 genes were identified in 68 of the 527 patients tested (13%). It is of interest that a quarter of those tested positive, did not have an extensive family history of breast/ovarian cancer but were diagnosed with early onset breast cancer, ovarian cancer under the age of 60 or triple negative breast cancer. The spectrum of mutations identified in our patient cohort is different compared to other Mediterranean countries. Furthermore, several of the mutations detected are novel and have not been identified in other ethnic populations. This highlights the importance of operating a national reference center for cancer genetic diagnosis which offers services tailored to the needs of the Cypriot population. Abstract :